Search for resonant diboson production in the [Formula: see text] final state in [Formula: see text] collisions at [Formula: see text] TeV with the ATLAS detector - ATLAS Collaboration; Aad, G; Abbott, B; Abdallah, J; Abdel Khalek, S; Abdinov, O; Aben, R; Abi, B; Abolins, M; AbouZeid, O S; Abramowicz, H; Abreu, H; et al. (The European physical journal. C, Particles and fields, 2015)
This paper reports on a search for narrow resonances in diboson production in the [Formula: see text] final state using [Formula: see text] collision data corresponding to an integrated luminosity of [Formula: see text] fb[Formula: see text] collected at [Formula: see text] TeV with the ATLAS detector at the Large Hadron Collider. No significant excess of data events over the Standard Model expectation is observed. Upper limits at the 95 % confidence level are set on the production cross section times branching ratio for Kaluza-Klein gravitons predicted by the Randall-Sundrum model and for Extended Gauge Model [Formula: see text] bosons. These results lead to the exclusion of mass values below 740 and 1590 GeV for the graviton and [Formula: see text] boson respectively.